Anterior Capsular Reconstruction Using a Dermal Allograft for an Irreparable Subscapularis Tear After Shoulder Arthroplasty: A Case Report. Issue 1 (January 2020) - Myers, Devon; Triplet, Jacob J.; Johnson, David B.; Strakowski, Jeffery A.; Wiseman, Stephen P.; Long, Nathaniel K.
Abstract : Case: A 51-year-old man was noted to have an irreparable subscapularis tear after total shoulder arthroplasty (TSA). Owing to positive reported results with superior capsular reconstruction, his insufficiency was addressed with anterior capsular reconstruction with use of a dermal allograft. Two-year follow-up results demonstrate good functional outcomes, no recurrent instability, and excellent patient satisfaction. Conclusions: Anterior shoulder insufficiency after TSA can significantly alter glenohumeral function and is an important cause of patient morbidity. This novel technique exhibits a good outcome and provides an alternative to previous methods of repair.